Productivity and the distribution of income to factors in Italy (1951-63) - DE MEO, G. (PSL Quarterly Review, 2014)
<!--[if gte mso 9]> 72 1024x768 <![endif]--> The article illustrates synthetically the main conclusions of a study on productivity and income distribution in Italy in the period 1951-63. The author considers partial and total productivity, total productivity measures, distribution of income factors, income from dependent labour and saving, output, total productivity, technical progress and capital intensity, disaggregation of technical progress, the capital-output ratio, changes in the demand structure, and income per unit of labour and per unit of capital. It is shown that the very considerable rise in productivity and real wages, as well as in employment, is the most significant feature of the prodigious progress made by the Italian economic system in recent years. Some policy implications are provided in the concluding remarks. JEL: E24, J24 <!--[if gte mso 9]> Normal 0 14 <![endif]--><!--[if !mso]> <![endif]--><!--[if gte mso 10]> <![endif]-->